Military and Water Governance Practices: A Theoretical Analysis of the Involvement of Indonesian National Armed Forces in the Citarum Harum Project in West Java, Indonesia - Mustabsyirotul Ummah Mustofa; Shafa Ghaisani Salsabila Brahmantika; Bima Riandy Tarigan (Centre for Asian Social Science Research (CASSR), Faculty of Social and Political Sciences, UIN Sunan Gunung Djati Bandung, 2021)
The Citarum Harum project as stated in Presidential Regulation No. 15/2018 was created as a response to a report that Citarum is “the dirtiest river in the world”. It is said that the complexity of the management of the Citarum river involves the Indonesian National Armed Forces (TNI) as the program implementer. This military involvement is claimed as a non-war military operation to increase the Citarum Harum program's effectiveness. However, in the discourse of Water Governance, the military is hardly mentioned as an engaged stakeholder, especially in the framework of